Anatomical Considerations and Emerging Strategies for Reducing New Onset Conduction Disturbances in Percutaneous Structural Heart Disease Interventions. Issue 4 (4th July 2021) - Albaghdadi, Mazen S.; Kadlec, Andrew O.; Sievert, Horst; Mahapatra, Srijoy; Romanov, Alexander; Siddiqui, Usman; Kronzon, Itzhak; Young, Michael Nguyen; Tzikas, Apostolos; Leon, Martin B.; Ho, Siew Yen; Kuck, Karl-Heinz
ABSTRACT: Transcatheter procedures offer an alternative to cardiac surgery in select patients with structural heart disease (SHD). Unfortunately, inadvertent disruption of electrical pathways and subsequent development of new onset conduction disturbances can occur in up to 5–70% of percutaneous interventions, result in pacemaker implantation, and confer a worse prognosis. The physical proximity between the conduction system (atrioventricular node, bundle of His, and bundle branches) and the site of percutaneous repair is increasingly recognized as a key factor influencing new onset conduction disturbance development in procedures located near the conduction system. This review covers the incidence, clinical significance, and mechanisms of new onset conduction disturbances and discusses current and emerging strategies to address this complication in these populations. Abbreviations: SHD: structural heart disease; AVN: atrioventricular node; AVB: atrioventricular block; LBBB: left bundle branch block; PPM: permanent pacemaker